Anemia tolerance versus blood transfusion on long-term outcomes after colorectal cancer surgery: A retrospective propensity-score-matched analysis - Weng, Meilin; Guo, Miaomiao; Li, Ting; Zhou, Changming; Sun, Caihong; Yue, Ying; Liao, Qingwu; Cai, Sanjun; Lu, Xihua; Zhou, Di; Miao, Changhong (Frontiers in Oncology, 2022)
Background Perioperative anemia and transfusion are intertwined with each other, and both have adverse impacts on the survival of colorectal cancer (CRC) patients. But the treatment of anemia still relies on transfusion in several countries, which leads us to question the effects of anemia tolerance and transfusion on the long-term outcomes of CRC patients. We investigated the combined effect of preoperative anemia and postoperative anemia and of preoperative anemia and blood transfusion, which imposes a greater risk to survival, to compare the effects of anemia tolerance and transfusion on overall survival (OS) and disease-free survival (DFS) in patients undergoing CRC surgery. Methods A retrospective propensity-score-matched analysis included patients with CRC undergoing elective surgery between January 1, 2008, and December 31, 2014. After propensity-score matching, Kaplan–Meier survival analysis and univariable and multivariable Cox proportional hazards models were used to study the prognostic factors for survivals. In univariate and multivariate Cox regression analysis, two novel models were built. Results Of the 8,121 patients with CRC, 1,975 (24.3%) and 6,146 (75.7%) patients presented with and without preoperative anemia, respectively. After matching, 1,690 patients remained in each group. In the preoperative anemia and postoperative anemia model, preoperative anemia and postoperative anemia was independent risk factor for OS (HR, 1.202; 95% CI, 1.043–1.385; P=0.011) and DFS (HR, 1.210; 95% CI, 1.050–1.395; P=0.008). In the preoperative anemia and transfusion model, preoperative anemia and transfused was the most dangerous independent prognostic factor for OS (HR, 1.791; 95% CI, 1.339–2.397; P<0.001) and DFS (HR, 1.857; 95% CI, 1.389–2.483; P<0.001). In patients with preoperative anemia, the OS and DFS of patients with transfusion were worse than those of patients without transfusion (P=0.026 in OS; P=0.037 in DFS). Conclusions Preoperative anemia and blood transfusion imposed a greater risk to OS and DFS in patients undergoing CRC surgery, indicating that the harm associated with blood transfusion was greater than that associated with postoperative anemia. These findings should encourage clinicians to be vigilant for the timely prevention and treatment of anemia, by appropriately promoting toleration of anemia and restricting the use of blood transfusion in patients with CRC.